Preparation of lysozyme-imprinted nanoparticles on polydopamine-modified titanium dioxide using ionic liquid as a stabilizer. Issue 26 (14th May 2019) - Zhao, Zhongliang; Zhu, Caihong; Guo, Qianping; Cai, Yan; Zhu, Xuesong; Li, Bin
Abstract : Molecular imprinting of proteins has evolved into an efficient approach for protein recognition and separation. Abstract : Molecular imprinting of proteins has evolved into an efficient approach for protein recognition and separation. However, maintaining the structural stability of proteins during the preparation process of molecularly imprinted polymers (MIPs) remains challenging. Ionic liquids (ILs), being capable of maintaining the stability of proteins, might enable effective imprinting and accurate recognition of proteins. In this study, lysozyme (Lyz)-imprinted titanium dioxide (TiO2 ) nanoparticles, TiO2 @Lyz-MIPs, have been successfully prepared for selective recognition and separation of Lyz. This was achieved by the free radical polymerization of hydroxyethyl acrylate (HEA) and poly(ethylene glycol) dimethacrylate (PEGDMA) on polydopamine (PDA)-modified TiO2 nanoparticles using an IL, choline dihydrogen phosphate (chol dhp), as the stabilizer of Lyz. It was found that both PDA modification of TiO2 and the use of chol dhp as stabilizer improved the adsorption capacity of TiO2 @Lyz-MIPs toward Lyz. When the concentration of HEA was 7 mg mL −1, the ratio of monomer to crosslinker was 20 : 1, and the concentration of chol dhp was 12.5 mg mL −1, the highest imprinting factor of 4.40 was achieved. TiO2 @Lyz-MIPs exhibited relatively high adsorption capacity with the maximum adsorption capacity up to 120 mg g −1, which was more than four times higher than that of the non-imprinted polymers (NIPs) counterpart, TiO2 @Lyz-NIPs. The adsorption rate of Lyz by TiO2 @Lyz-MIPs was also much higher than that of TiO2 @Lyz-NIPs. TiO2 @Lyz-MIPs could successfully separate Lyz from diluted egg white, a complex mixture of proteins. Findings from this study indicate that effective recognition cavities toward Lyz were formed on the surface of Lyz-imprinted TiO2 nanoparticles prepared using IL as the template stabilizer. This approach may facilitate the development of MIPs for efficient protein recognition and separation.